Developing Organization Skills: Tingkatkan Komunikasi Efektif dalam Berorganisasi Menggunakan Metode Experiental Learning - Dian Dwi Nur Rahmah; Netty Dyan Prastika; Putri Marsha Nasywa Salsabila; Arti Wulan Cantika (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Every organization needs effective communication in carrying out the organization's vision and mission. The purpose of this training is increase participants' understanding of effective communication in organizations. The training was held at the Pancasila and Citizenship Education Student Association at Mulawarman University with 37 participants. The data collection process to identify problems is interviews, observations, and questionnaires. The method used is experiential learning based on direct experience and oriented towards participants using lecture methods, question and answer sessions, ice breaking, and FGD. Based on the training results, the post-test score was 16.2% greater than the pretest score. Supported by the results of t test calculations in SPSS software, it is known that Sig. (2-tailed) is 0.000 < 0.05 and there is a significant difference between before and after the training given to participants. The conclusion is that there is an increase in understanding of effective communication among the training participants.